Assessing electrogenetic activation via a network model of biological signal propagation - Chun, Kayla; VanArsdale, Eric; May, Elebeoba; Payne, Gregory F.; Bentley, William E. (Frontiers in Systems Biology, 2024)
Molecular communication is the transfer of information encoded by molecular structure and activity. We examine molecular communication within bacterial consortia as cells with diverse biosynthetic capabilities can be assembled for enhanced function. Their coordination, both in terms of engineered genetic circuits within individual cells as well as their population-scale functions, is needed to ensure robust performance. We have suggested that "electrogenetics", the use of electronics to activate specific genetic circuits, is a means by which electronic devices can mediate molecular communication, ultimately enabling programmable control. Here, we have developed a graphical network model for dynamically assessing electronic and molecular signal propagation schemes to better understand our previous experimental results, but also to enable future designs wherein subpopulation composition, genetic circuits, and spatial configurations can be varied to tune performance. We found that networks with more distinct subpopulations (high network modularity) propagated signals more slowly than randomized networks, while strategic arrangement of subpopulations with respect to the inducer source (the electrode) can increase signal output and outperform otherwise homogeneous networks.